Empirical Studies on COTS Methodology - kumar, Reena Pradeep (International Journal of Computer Sciences and Engineering, 2025)
Commercial Off-The-Shelf (COTS) components are being used in increasing number to reduce cost and delivery time of software. A commercial Off-The-Shelf (COTS) component is becoming more and more important since it promotes reuse to higher levels of abstraction. As a consequence, many components are available either being open-source software (OSS) or commercial-off-the shelf (COTS). Component - Based Software Development has evolved as a popular software development technique since the introduction of Microsoft’s Component Object Model (COM) in the early 90s. This paper presents review literature that has been published on empirical research of COTS. We were interested to describe the empirical research on COTS to see that if there are any areas of CBSD that are yet to be touched in the research process. Empirical studies are the proofs of the hypothesis about the industry’s perception of CBSD process